2022
DOI: 10.3390/nu14030446
|View full text |Cite
|
Sign up to set email alerts
|

Combined Phyllostachys pubescens and Scutellaria baicalensis Prevent High-Fat Diet-Induced Obesity via Upregulating Thermogenesis and Energy Expenditure by UCP1 in Male C57BL/6J Mice

Abstract: This study examined the anti-obesity effects of a Phyllostachys pubescens (leaf) and Scutellaria baicalensis root mixture (BS21), and its underlying mechanisms of action, in high-fat diet (HFD)-induced obese mice. Mice were fed a HFD with BS21 (100, 200, or 400 mg/kg) for 9 weeks. BS21 reduced body weight, white adipose tissue (WAT) and liver weights, liver lipid accumulation, and adipocyte size. Additionally, BS21 reduced serum concentrations of non-esterified fatty acid, triglyceride, glucose, lactate dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Adipogenesis increases cell number by inducing C/EBPα and PPARγ to promote the differentiation of preadipocytes [ 18 ], whereas lipogenesis increases fat cell size by inducing ACC1, FAS, and SREBP-1C to promote fatty acid synthesis [ 19 ]. Moreover, recent studies have shown that increasing energy expenditure via thermogenesis involving UCP1 and AMPK is a promising strategy for combating obesity [ 20 ]. Consequently, the regulation of white fat browning and lipid metabolism, including adipogenesis and lipogenesis, has emerged as a potential anti-obesity target [ 21 ] and is being studied as a mechanism underlying the anti-obesity efficacy of numerous natural bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Adipogenesis increases cell number by inducing C/EBPα and PPARγ to promote the differentiation of preadipocytes [ 18 ], whereas lipogenesis increases fat cell size by inducing ACC1, FAS, and SREBP-1C to promote fatty acid synthesis [ 19 ]. Moreover, recent studies have shown that increasing energy expenditure via thermogenesis involving UCP1 and AMPK is a promising strategy for combating obesity [ 20 ]. Consequently, the regulation of white fat browning and lipid metabolism, including adipogenesis and lipogenesis, has emerged as a potential anti-obesity target [ 21 ] and is being studied as a mechanism underlying the anti-obesity efficacy of numerous natural bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%